If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-3=14x
We simplify the equation to the form, which is simple to understand
2x-3=14x
We move all terms containing x to the left and all other terms to the right.
+2x-14x=+3
We simplify left and right side of the equation.
-12x=+3
We divide both sides of the equation by -12 to get x.
x=-0.25
| 6x^4-7x^3+8x^2-7x+2=0 | | 1.4-3=2+h | | x^4+2x+2=0 | | 0.3(k-0.2)=0.6 | | 5x^2-4x-2=0 | | 12+3x=x | | 8x^3+6x^2-5x+1=0 | | 140-7x=29x+16 | | 2x-9=x | | -3x-1-5x+4= | | t^2=3t+7 | | 9-7x=108-28x | | 9-2x=x | | 6+5x=x | | x-2(x-1)=4-3(x-2) | | 13-8z=7 | | 12+5=11+12x | | -3(x-7)+2= | | 9(2-a)=63 | | 3(2+5m)=-54 | | 17(x-2)=34 | | 17(x-2)= | | 10-2(x+3)=3+3(2x+5) | | 4b-(9b-8)= | | 3x^2+10x+5=0 | | 379.94=3.14*r^2 | | 4+45=8x+13 | | 2x-5x=x+8 | | 4x+10=2x+29 | | -7y-(2y+4)= | | 4x^2+13=3 | | 2x^2=162 |